Differential Diel Translation of Transcripts With Roles in the Transfer and Utilization of Iron-Sulfur Clusters in Arabidopsis - Zhang, Hongliang; Krämer, Ute (Frontiers in Plant Science, 2018)
Iron-sulfur (Fe-S) clusters are evolutionarily ancient ubiquitous protein cofactors which have mostly catalytic functions but can also have structural roles. In Arabidopsis thaliana, we presently know a total of 124 Fe-S metalloproteins that are encoded in the genome. Fe-S clusters are highly sensitive to oxidation. Therefore, we hypothesized that Fe-S cluster protein biogenesis is adjusted following the daily rhythms in metabolism driven by photosynthesis at the whole-plant, organ, cellular and sub-cellular levels. It had been concluded previously that little such regulation occurs at the transcript level among the genes functioning in Fe-S cluster assembly. As an initial step towards testing our hypothesis, we thus addressed the diel time course of the translation state of relevant transcripts based on publicly available genome-wide microarray data. This analysis can answer whether the translation of the pool of transcripts of a given gene is temporarily either enhanced or suppressed, and when during the day. Thirty-three percent of the transcripts with functions in Fe-S cluster assembly exhibited significant changes in translation state over a diurnal time course, compared to 26% of all detected transcripts. These transcripts comprised functions in all three steps of cluster assembly including persulfide formation, Fe-S cluster formation and Fe-S cluster transfer to target apoproteins. The number of Fe-S cluster carrier/transfer functions contributed more than half of these transcripts, which reached maxima in translation state either during the night or the end of the night. Similarly, translation state of mitochondrial frataxin and ferredoxin, which are thought to contribute Fe and electrons during cluster formation, peaked during the night. By contrast, translation state of chloroplast SUFE2 in persulfide formation and cytosolic Fe-S cluster formation scaffold protein NBP35 reached maxima in translation state during the day. Among the other group of transcripts encoding target Fe-S cluster-utilizing proteins, 19% exhibited diurnal variation in translation state. Day-time maxima of translation state were most common among these transcripts, with no maximum during the night. We conclude that diurnal regulation of translation state is important in metalloprotein biogenesis. Future models of Fe-S protein biogenesis require more comprehensive data and will have to accommodate diurnal dynamics.